Applications the Drug Selsoviet with a Combination of Retinal amine in Retinal Dystrophy - Usmanova Tulganoy Jaloliddinovna (Zien Journals, 2022)
The article explains the scientific significance of retinal dystrophy. An actual problem in ophthalmology at the present time is retinal dystrophy (DS). This is due to the progressive increase in the incidence of this pathology.
Keywords: Retinal dystrophy; OCT; Goniolinza